A killer Christmas : a murder, she wrote mystery - Fletcher, Jessica; Moran, Terrie Farley (Fletcher, Jessica. Murder, she wrote., 2024)
"It's Christmastime in Cabot Cove, but there's more homicide than ho-ho-ho in the newest entry in the USA Today bestselling Murder, She Wrote series. Christmas is not an easy time to sell a house, but in Boston tycoon John Bragdon, Cabot Cove Realtor Eve Simpson has found a buyer for the old Jarvis homestead. Unfortunately, Eve gets a lump of coal in her stocking in the form of Kenny Jarvis, who has been missing for years and presumed dead but has now come back to stop his sister from selling their childhood home. Eve presses on, organizing a welcome dinner for Bragdon and his wife, Marlene, to meet the leading citizens of the town, including Jessica Fletcher. Dinner is interrupted by an uninvited guest - not Santa but Kenny, who threateningly promises Marlene she will never live in his house. When Marlene is found dead a few days later, Kenny is the natural suspect. But Jessica isn't so sure he's on the naughty list"--